2008
DOI: 10.1161/strokeaha.107.506816
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Efficacy of Granulocyte-Colony Stimulating Factor in Animal Models of Focal Cerebral Ischemia

Abstract: Background and Purpose-Recent reports have described the efficacy of the hematopoietic growth factor granulocytecolony stimulating factor (G-CSF) in animal stroke models. Early clinical multicenter trials evaluating the effect of G-CSF in acute stroke and pilot clinical trials for the subacute phase are ongoing. To guide further development, a meta-analysis was performed to assess the effects of G-CSF on infarct size and sensorimotor deficits. Methods-Using electronic and manual searches of the literature, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 41 publications
2
88
0
3
Order By: Relevance
“…112 Our meta-regression analysis revealed a clear doseresponse relationship of the efficacy of G-CSF. 112 When administered within the first 6 hours after the induction of ischemia, G-CSF reduced infarct sizes by 0.8% per 1 g/kg body weight and by 2.1% per 1 g/kg body weight when applied later than 6 hours. 112 Based on these promising preclinical studies, a number of clinical studies were initiated to test the efficacy of G-CSF in stroke patients.…”
Section: G-csfmentioning
confidence: 72%
See 2 more Smart Citations
“…112 Our meta-regression analysis revealed a clear doseresponse relationship of the efficacy of G-CSF. 112 When administered within the first 6 hours after the induction of ischemia, G-CSF reduced infarct sizes by 0.8% per 1 g/kg body weight and by 2.1% per 1 g/kg body weight when applied later than 6 hours. 112 Based on these promising preclinical studies, a number of clinical studies were initiated to test the efficacy of G-CSF in stroke patients.…”
Section: G-csfmentioning
confidence: 72%
“…[107][108][109][110][111] To obtain an overall impression of the efficacy of G-CSF in preclinical studies and to evaluate conditions under which maximum efficacy can be achieved, we performed a meta-analysis and meta-regression analysis of G-CSF in animal stroke models. 112 We showed that G-CSF reduced both infarct volumes and sensorimotor deficits. 112 Our meta-regression analysis revealed a clear doseresponse relationship of the efficacy of G-CSF.…”
Section: G-csfmentioning
confidence: 81%
See 1 more Smart Citation
“…Numerous reports have described the efficacy of G-CSF in animal models of different neurological diseases including stroke (Schabitz et al, 2003;Schneider et al, 2005;KomineKobayashi et al, 2006;Solaroglu et al, 2006;Minnerup et al, 2008), Parkinson's disease (Cao et al, 2006;Meuer et al, 2006), and Alzheimer's disease (Tsai et al, 2007). These studies confirm G-CSF as a neurotrophic factor, and ascertained its role in neuroprotection and neuroregeneration relevant to the most prominent neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 84%
“…This former review observed a 0.8% reduction in infarct volume per 1 g/kg increase in G-CSF dose (Minnerup et al, 2008). However, it included fewer articles (13 publications), excluded studies appropriate for analysis (Hermann and Kilic, 2008;Sehara et al, 2007c;Taguchi et al, 2007) and found no evidence of publication bias.…”
Section: This Systematic Review Finds That G-csf Reduces Lesion Size mentioning
confidence: 95%